2021
DOI: 10.1002/adsu.202100159
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cu and Leaf Nanostructure‐Based Photothermal Biomaterial for Efficient Solar Steam Generation

Abstract: Solar steam generation (SSG) is promising for clean water production owing to low cost, simple operation, and green technology. This work investigates the fabrication of bioinspired photothermal (BIPT) material by sputtering a copper layer on Phanera purpurea (PP) leaf for application in SSG systems. It is observed that the light absorbance of the BIPT material exceeds 92% in the wavelength region of 300–2500 nm. This is due to the light trapping effect caused by multi‐internal reflection inside the Cu‐coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For instance, Chen et al [58] demonstrated a Cu-based photothermal material by a simple chemical oxidation treatment on Cu foam, which showed superior ability on SSG as well as salt-resistance. Tien Thanh Pham et al [59] fabricated bioinspired photothermal material by sputtering a Cu layer on the leaf for the SSG system and it exhibited a high light absorbance of over 92%, resulting in a high solar steam efficiency and water evaporation rate.…”
Section: Pure Metalsmentioning
confidence: 99%
“…For instance, Chen et al [58] demonstrated a Cu-based photothermal material by a simple chemical oxidation treatment on Cu foam, which showed superior ability on SSG as well as salt-resistance. Tien Thanh Pham et al [59] fabricated bioinspired photothermal material by sputtering a Cu layer on the leaf for the SSG system and it exhibited a high light absorbance of over 92%, resulting in a high solar steam efficiency and water evaporation rate.…”
Section: Pure Metalsmentioning
confidence: 99%
“…The evaporation test was carried out using seawater from Bohai Sea in China, and the content of Cl − and Br − measured after evaporation met the standard of seawater desalination. Pham et al 149 fabricated a bioinspired PM by sputtering copper layers on plant leaves, finding that its EE was 83.7% and ER was 1.45 kg m −2 h −1 . Then, desalination experiments were carried out on seawater from the Vietnam Sea, and it was determined that the concentration of anions (Cl − , SO 4 2− , and NO 3− ) was reduced by more than 99.99% after purification.…”
Section: Removal Of the Pollutants From Water By Sdiementioning
confidence: 99%
“…Several strategies have been proposed to improve the efficiency of SSG by engineering photothermal materials to have strong light absorption over a wide-frequency band (0.2–3 μm) and high photothermal conversion efficiency, as well as designing a substrate to have good thermal insulation to avoid excessive heat loss and capability to supply water to hot regions. They include chemical regulation ,, and structural engineering , of the photothermal materials as well as solar evaporator design. , Chemical regulation of photothermal materials is carried out by introducing different elements or functional groups into the primary photothermal material or compositing two or more photothermal materials. Structural engineering includes assembling photothermal materials to specific architecture for the efficient use of the materials in the solar steam generation system.…”
Section: Solar Thermal Conversion Materialsmentioning
confidence: 99%